Duration of extinction trials as a determinant of instrumental extinction in terrestrial toads (Rhinella arenarum) - Puddington, Martin Miguel (2018)
Instrumental learning guides behavior toward resources. When such resources are no longer available, approach to previously reinforced locations is reduced, a process called extinction. The present experiments are concerned with factors affecting the extinction of acquired behaviors in toads. In previous experiments, total reward magnitude in acquisition and duration of extinction trials were confounded. The present experiments were designed to test the effects of these factors in factorial designs. Experiment 1 varied reward magnitude (900, 300, or 100 s of water access per trial) and amount of acquisition training (5 or 15 daily trials). With total amount of water access equated in acquisition, extinction with large rewards was faster (longer latencies in 900/5 than 300/15), but with total amount of training equated, extinction with small rewards was faster (longer latencies in 100/15 than 300/15). Experiment 2 varied reward magnitude (1200 or 120 s of water access per trial) while holding constant the number of acquisition trials (5 daily trials) and the duration of extinction trials (300 s). Extinction performance was lower with small, rather than large reward magnitude (longer latencies in 120/300 than in 1200/300). Thus, instrumental extinction depends upon the amount of time toads are exposed to the empty goal compartment during extinction trials.